Resource and cost management - Gavrys, O.; Gaponenko, O.; Sergienko, O. (My University, 2017)
Educational lecture notes contains the fundamentals of a general theory of resource and cost management, classification of costs for decision-making, methods of constructing cost functions of the enterprise, analysis of the relationship between costs, volume and profits, the methods and systems of cost calculation, principles of cost management system. Designed for students directions 073 «Management» and 076 «Entrepreneurship, trade and exchange activity».
Keywords: economics; cost management; enterprises; production; costs dynamics; cost management systems